14. EFFECTIVE TREATMENT OF ENDOMETRIOSIS WITH PLASTIC PARTICLES (PVA) AND BIOLOGICAL GLUE BY THE METHOD OF UTERINE ARTERY EMBOLIZATION UNDER C-ARM ANGIOGRAPHY AT TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
1